Feminist Kyai, K.H. Husein Muhammad: The Feminist Interpretation on Gendered Verses and the QurâÄn-Based Activism - Rahman, Yusuf (Al-Jamiah: Journal of Islamic Studies, 2017)
Husein Muhammad, a feminist âÄlim or kyai of Dar al-Tauhid Islamic boarding school in Arjawinangun Cirebon, West Java, Indonesia, has written various articles and books on women issues and gender problem. Growing up in a conservative family, and graduating from Al-Azhar University, kyai Husein becomes one of the main proponents of Islamic feminism in Indonesia. Apart from leading a pesantren (Islamic boarding school), in 2000 kyai Husein established Fahmina Institute, an NGO which strives to promote community empowerment and gender justice based on pesantren tradition, and Fahmina Islamic Studies Institute, an Islamic higher education, which aims to build a tolerant and unprejudiced Indonesian Islam. This article discusses his approach in reinterpreting the QurâÄnic verses and Islamic traditions on women issues, and his contribution in the light of the discourse of gender and feminism in Islam as well as in mainstreaming gender in Indonesia.Â [KH Husein Muhammad merupakan ulama feminis, pengasuh Pondok Pesantren Dar al-Tauhid Arjawinangun Cirebon Jawa Barat, yang telah menghasilkan banyak tulisan dan buku terkait persoalan perempuan dan masalah gender. Beliau yang dibesarkan dalam keluarga tradisional dan lulusan Universitas Al-Azhar, kini telah menjadi tokoh utama feminis Islam di Indonesia. Disamping menjadi pemimpin pondok pesantren, beliau mendirikan Fahmina Institute pada tahun 2000 yang merupakan sebuah LSM pemberdayaan masyarakat dan keadilan gender berbasis pesantren tradisional. Selain itu juga mendirikan Fahmina Islamic Studies Institute, sebuah perguruan tinggi Islam yang bertujuan membangun toleransi dan mengikis prasangka Islam Indonesia. Tulisan ini membahas pendekatannya dalam menafsirkan ayat al Qurâan dan tradisi Islam mengenai persoalan perempuan serta kontribusinya dalam pencerahan wacana gender dan feminisme dalam Islam terutama pengarusutamaan gender di Indonesia.]